Secure Pesticide Storage: General Features - Frederick M. Fishel (EDIS)
Revised! PI33, a 10-page illustrated fact sheet by Frederick M. Fishel, combines and supersedes five fact sheets in the Secure Pesticide Storage series. It provides an overview of the general features required in a pesticide storage facility. Includes a pesticide storage checklist and additional resources. Published by the UF Department of Agronomy, October 2009.